2023
DOI: 10.1002/fft2.301
|View full text |Cite
|
Sign up to set email alerts
|

Olfr78, a novel short‐chain fatty acid receptor, regulates glucose homeostasis and gut GLP‐1 secretion in mice

Yanan Wang,
Mengjie Li,
Jingya Guo
et al.

Abstract: Olfr78, which is a novel receptor for short‐chain fatty acid (SCFA) acetate and propionate, plays essential roles in some cellular processes. The present study aimed to investigate the role of olfr78 in regulating energy metabolism and delineate the underlying mechanisms using olfr78−/− mice. Deletion of olfr78 did not influence the adiposity of mice fed either normal chow or a high‐fat diet (HFD). However, olfr78−/− mice exhibited glucometabolic dysfunction, as evidenced by increased fasting blood glucose lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…In contrast, a high-fat or low-fiber diet would promote the growth and proliferation of detrimental bacteria, accumulating toxins such as bacterial endotoxins and shiga toxins in the intestinal tract (Daien et al, 2017). With the intervention of DF, the levels of metabolites such as short-chain fatty acids (SCFAs) in the gut increased, which could enhance the stability of the intestinal barrier and facilitate intestinal immune function (Koh et al, 2016;Wang et al, 2023). Moreover, current research has revealed that SCFAs could penetrate the bloodstream to improve immunity and regulate glucolipid metabolism (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a high-fat or low-fiber diet would promote the growth and proliferation of detrimental bacteria, accumulating toxins such as bacterial endotoxins and shiga toxins in the intestinal tract (Daien et al, 2017). With the intervention of DF, the levels of metabolites such as short-chain fatty acids (SCFAs) in the gut increased, which could enhance the stability of the intestinal barrier and facilitate intestinal immune function (Koh et al, 2016;Wang et al, 2023). Moreover, current research has revealed that SCFAs could penetrate the bloodstream to improve immunity and regulate glucolipid metabolism (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%